Ecumenical Social Ethics and Action in a Fractured World: Celebrating a Century of Commitment to the People of the World - Gnanadason, Aruna (The ecumenical review, 2024)
This article discusses the history of ecumenical social ethics and action since the Universal Christian Council on Life and Work in Stockholm in 1925, and especially the work of the Church and Society programme of the World Council of Churches following its founding in 1948. It recounts how in the 1960s, perspectives on ecumenical social ethics were challenged by voices from Africa, Asia, and Latin America. The article examines especially the role played by women in the search for just structures in church and society and in seeking to respond to the challenges of globalization. It concludes with a discussion of the Theology of Life programme in the 1990s and the process to find Alternatives to Globalization Addressing People and the Earth (AGAPE).